Investigation of tangential force on ball nose rake face during high-speed milling of Inconel 718. Issue 3 (3rd July 2018) - Kasim, M. S.; Che Haron, C. H.; Ghani, J. A.; Izamshah, R.; Akmal, M.; Ali, M. A.; Hadzley, M.; Salleh, M. S.
Abstract: Notch wear and flaking are common tool damage found during end milling. The problems are caused by abrasive wear and excessive cyclic load exerted on cutting tool. This study presents an experimental investigation on the effect of various cutting parameters in high-speed machining of aged Inconel 718 on the tangential force. The effect of cutting speed, feed rate, depth of cut and width of cut on cutting forces had been studied. The cutting parameters were cutting speed, Vc  of 100–140 m/min, feed rate, fz  of 0.1–0.2 mm/tooth, depth of cut, ap of 0.5–1.0 mm and width of cut, ae of 0.2–1.8 mm. The results show that the width of cut is the main factor in controlling tangential force during end milling, followed by depth of cut and feed rate. These factors controlling the volume of material removed so that larger stress created on the cutter rake face.